2020
DOI: 10.3390/molecules25204650
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometric Analysis of Inflammation Dynamics in the Periodontium Following the Use of Fixed Dental Prostheses

Abstract: Cytomorphometry is used in the sampling of biological materials and diagnostic procedures. The use of cytological studies in periodontal diseases is not well described in the literature. Our study aimed to quantitatively assess the inflammation dynamics using cytomorphometric analysis of the periodontium before and after the use of fixed dental prostheses. Following ethics approval, a total of 105 subjects were divided in 3 groups as gingivitis (n = 23), periodontitis (n = 58), and healthy periodontium (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
0
30
1
2
Order By: Relevance
“…Cytomorphometric analysis is a cytological study that may enable the selection of the most appropriate prostheses for patients with existing periodontal pathologies [ 38 , 39 ]. Recently, Heboyan et al [ 39 ] assessed the inflammation dynamics using a cytomorphometric analysis of the periodontium before and after the use of fixed dental prostheses and reported no significant changes in the parameters among patients with a healthy periodontium, before and after prosthetic treatment and regardless of the prosthesis type used. In all study groups, there was a statistically significant increase ( p < 0.05) in the oral epithelial cell counts and a statistically significant decrease ( p < 0.05) in the PMN count following the insertion of the fixed prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomorphometric analysis is a cytological study that may enable the selection of the most appropriate prostheses for patients with existing periodontal pathologies [ 38 , 39 ]. Recently, Heboyan et al [ 39 ] assessed the inflammation dynamics using a cytomorphometric analysis of the periodontium before and after the use of fixed dental prostheses and reported no significant changes in the parameters among patients with a healthy periodontium, before and after prosthetic treatment and regardless of the prosthesis type used. In all study groups, there was a statistically significant increase ( p < 0.05) in the oral epithelial cell counts and a statistically significant decrease ( p < 0.05) in the PMN count following the insertion of the fixed prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…In this type of prosthesis, inflammatory processes in periodontium do not occur, quickly improving the marginal fit and reducing the risk of formation of dental biofilm. In addition, zirconium dioxide is biocompatible with the mucous membranes and tissues of the oral cavity [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heboyan et al [ 8 ] studied inflammation dynamics using cytomorphometric analysis of the periodontium before and after the use of fixed dental prostheses using the conventional method (C/M/CoCr), cobalt-chrome metal-ceramic prostheses using the CAD/CAM technique (C/C/CoCr), and zirconia-based ceramic prostheses using the CAD/CAM technique (C/C/Zr) among subjects with gingivitis and periodontitis. They found that regardless of prostheses type used, no significant change in the parameters was identified among patients with a healthy periodontium, before and after prosthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations